Tech in sight three ways to move people- fast, faster, fastest. - Guizzo, E. (IEEE spectrum)
Here we are in the future, yet we're still wasting time stuck in traffic and trussed in a pressurized cabin for long hours in flight. For the speed boost that was promised us in so many futuristic movies, look to these three technologies.